Pembelajaran Jarak Jauh Bagi Anak Tunarungu Pada Masa Pandemi Covid-19 di SLB Al Azhar Bukittinggi - Monika Yeyen Asvira; Nurhastuti Nurhastuti (Jurnal Penelitian Pendidikan Khusus, 2021)
The background of this research found problems in the learning system in schools from face-to-face learning to distance learning due to the Covid-19 pandemic, both regular schools and special schools (SLB). This study aims to describe how the planning, implementation, supporting factors and inhibiting factors for the implementation of distance learning for deaf children in SLB Al Azhar Bukittinggi. This study used descriptive qualitative method. The results showed that: 1) Planning by compiling a program includes essential materials and the ability of teachers to use technology, 2) Implementation using online and offline methods with a strategy of utilizing technology, 3) Supporting factors include collaboration between schools and parents, assistance from the school and free quota assistance from the government, 4) The inhibiting factors for implementing distance learning are parents who have permanent jobs, parents who do not understand the task, and where students live who find it difficult to get an internet network.